Characterization of ablation dimensions in magnetic resonance-guided laser interstitial thermal therapy via a semi-automated algorithm - Liang, Allison S.; Munier, Sean M.; Patel, Nitesh V.; Danish, Shabbar F. (Interdisciplinary neurosurgery : Advanced techniques and case management, 2020)
Magnetic resonance-guided laser interstitial thermal therapy (MRgLITT) is a minimally invasive procedure that produces real-time thermal damage estimates (TDE) in orthogonal MRI-planes. The current system does not allow the user to quantify the TDE during the ablation process. We aim to characterize TDE dimensional expansion via a validated semi-automated algorithm. Selection criteria included single-laser catheter use, performed with the Visualase MRI-Guided Laser Ablation System. TDE lengths and widths relative to the laser path were calculated using a developed algorithm and validated with two raters’ manual measurements. MATLAB Blob Analysis was used to approximate TDE ellipsoidal major-minor axes. TDE length–width expansion was characterized by the power law f(x) = axk. For analyses of 40 TDEs across 20 patients, minimal measurement differences, <1.0 mm, were observed between algorithm vs raters (P > 0.2). No significant differences were observed between ratios of major-minor axes vs length–width (P = 0.19). For dynamic studies, 60 MRI planes across 30 patients were analyzed for linear regressions (R^2 = 0.70–0.99) from log-log plots of TDE dimensions vs time. Constant “a” for width (0.38 ± 0.17) was larger than length (0.28 ± 0.16) (P < 0.001). Constant “k” for length (6.3 ± 3.1) was larger than width (2.5 ± 1.4) (P < 0.001). Final lengths (19.1 ± 2.5 mm) were larger than widths (14.2 ± 2.4 mm) (P < 0.001). Our algorithm and dimensional analyses lays the essential groundwork for ongoing studies to extract real-time TDE data during the ablation process. Ultimately, TDE cross-sectional geometric data should allow estimation of ablation volumes via a definite integral method.